Bandwidth management in universities in Zimbabwe: Towards a responsible user base through effective policy implementation - Chitanana, Lockias (International Journal of Education and Development using Information and Communication Technology; Bridgetown, 2012)
This research was undertaken to investigate the issue of how to maximise or make efficient use of bandwidth. In particular, the research sought to find out about what universities in Zimbabwe are doing to manage their bandwidth. It was, therefore, appropriate to survey a sample of five universities and to catalogue their experiences. Results show that most universities in our sample did not have an official Acceptance Use Policy (AUP) to assist with bandwidth management. Successful provision of managed network bandwidth within a university is likely to involve the application of many tools encompassing a number of different techniques. These products are often expensive and are rarely available for loan. Fortunately, a cost-effective solution exists for all universities that can be deployed regardless of the campus' existing network configuration or installed devices. The authors recommend that using Quality of Service (QoS) and Bandwidth management will enable network administrators to control network traffic flow so that appropriate users and applications get priority during the allocation of network resources. Also, universities must contain in their IT policies a meaningful AUP which will help universities to develop and refine usage and access as well as plan for network resource allocation. [PUBLICATION ABSTRACT]
EdTechHub.ItemAlsoKnownAs: 2129771:5WFXCS4Y
Keywords: Bandwidths; College campuses; Computers; Education; Internet access; Internet resources; Product introduction; Research; __C:filed:1; ⛔ No DOI found